Bureaucratic Reform in Organizing and Managing Adaptive, Accountable, and Competency-Based Civil Servants Based on 'World-Class Smart Civil Servants’ - Tauhid, Tauhid; Taufiq, Muhammad; Ma'sud, Mas'ud; Yasin, Haerun (Jurnal Studi Ilmu Pemerintahan, 2023)
The research focuses on enhancing the State Civil Apparatus (ASN) at the Human Resources Development Agency for the City of Bima, aiming to achieve world-class standards. The study addresses challenges, including low competence, limited innovation, inadequate IT and foreign language proficiency, and a constrained entrepreneurial mindset. Employing a descriptive qualitative approach, the research involves interviews with key informants such as the Regional Secretary, Government Assistant, Social Welfare representative, Head of BPSDM, and Head of the Competency Development Division. Additionally, observation and documentation methods were utilized to explore and resolve the research problems. The findings reveal that the current bureaucratic reform measures to develop the State Civil Apparatus into a world-class ASN have not been effective and have yet reached their full potential. Improvements in ASN achievements are essential within the framework of SMART ASN. Identified as the main obstacles to achieving world-class status by 2024 are the existing capacities of ASN, including professionalism, IT and foreign language proficiency, global awareness, and entrepreneurial spirit. In light of these findings, the study proposes implementing more stringent policies within the ASN community to yield more satisfactory outcomes in their journey toward becoming world-class innovative civil servants.